Two new diterpenoid quinones with lung protective activity from the roots of Salvia miltiorrhiza. (October 2022) - Ren, Ying-Jie; Cao, Yan-Gang; Zeng, Meng-Nan; Zhang, Qin-Qin; Liu, Yan-Ling; Chen, Xu; Fan, Xi-Ling; Li, Xiang-Da; He, Chen; Zheng, Xiao-Ke; Feng, Wei-Sheng
Abstract: Two new diterpenoid quinones, salvianolactone acid J and K (1 and 2 ), as well as eight known compounds (3 –10 ) were isolated from the roots of Salvia miltiorrhiza . Their structures were elucidated by comprehensive analysis. All compounds (1 -10 ) were evaluated for their protective effects against the BEAS-2B cells injury induced by LPS in vitro and compounds 1, 3, and 4 showed significantly protective activity at the concentration of 10 μM. Besides, compounds 1, 3, and 4 ameliorated the nuclear transport of p-P65 in LPS-induced BEAS-2B cells. Graphical Abstract: ga1 Highlights: Two new diterpenoid quinones were isolated from the dried roots of Salvia miltiorrhiza . All the isolated compounds were evaluated in vitro for their lung-protective effects. Compounds 1, 3, and 4 significantly displayed protective effect against the BEAS-2B cells injury induced by LPS.